combine the like terms

4a+7b+3-2a+3b-2

### Want to see the full answer?

Check out a sample Q&A here*star_border*

## Related Algebra Q&A

Find answers to questions asked by students like you.

Q: Combine the like terms: 6a-2b-2a+1b

A: Solution:-

Q: Simplify by Combining Like Terms: 5n -n-3+12d-6-3d + (-12d)

A: To combine the liked terms

Q: Simplify by combining like terms. (6x2 + 3x2y2) + (4x2y2 − 9x2)

A: Given, (6x2 + 3x2y2) + (4x2y2 − 9x2)

Q: Simplify 6x2 - 3x - 7x2 - 5x - 2 by combining similar terms.

A: Simplify 6x2-3x-7x2-5x-2 by combining similar terms.

Q: Combine like terms. -2x - 2 y - 5a + 7y'- 3

A: The given expression is, -2x-2-y3-5x+7y3-3-x. Simplify the given expression by combining the like…

Q: Identify the expression that is not equivalent to the others x-2+3x , 4(x-2) , -2+7x-3x , 4x-2

A: We have to simplify each expression.x-2+3x= 4x-2 (combined x+3x=4x)4(x-2) = 4x-8 (distributed 4)

Q: Combine like terms to create an equivalent expression. -1/2 (-3y+10)

A: Click to see the answer

Q: Find an expression which represents the difference when (-2x-8y) is subtracted from (-3x-7y) in…

A: Click to see the answer

Q: -2 (b) 5x-5

A: Click to see the answer

*question_answer*

Q: -2 (b) 5x-5

A: We will solve the above problem.

*question_answer*

Q: Combine like terms to create an equivalent expression. 1 (-3y + 10)

A: Given-12(-3y+10)

*question_answer*

Q: Reduce the expression to lowest terms. [ (4x + 1) . 5 - (5x - 2) . 4 ] / (5x - 2) 2

A: Here we have to Reduce the expression to the lowest terms. (4x+1)·5-(5x-2)·4(5x-2)2

*question_answer*

Q: you're comförtablé with. y = Ce-3x – 2Cze-3x

A: Given: y=C1e-3x-2C2e-3x To eliminate the arbitrarty constant.

*question_answer*

Q: Simplify 3 - 4y + (-7y) + 7.4

A: Simplification

*question_answer*

Q: Answer with true @/ /2x-5/4 then 2 false or

A: To find Whether the given statement is true or false

*question_answer*

Q: Which of the functions satisfy the hypotheses of theMean Value Theorem on the given interval, and…

A: Given The function is f(x)=x2-x-2≤x≤-12x2-3x-3-1<x≤0 Mean value theorem :- let f be the…

*question_answer*

Q: (2yx³)~³ (-3yx²)-2 -3

A: Concept - (abc)^n = (a^n)(b^n)(c^n)

*question_answer*

Q: Unite the following (7x^2+x+9)-(3x^2-4)

A: (7x^2+x+9)-(3x^2-4) = (7x2+x+9)-(3x2-4)

*question_answer*

Q: -5 4 -3 -2 to

A: To determine which of the given graphs are of one-to-one function

*question_answer*

Q: Simplify by combining like terms. 12y + 9y - 2y? - 9y? 12y + 9y - 2y? - 9y? =0

A: 12y+9y-2y^2-9y^2 = 21y-11y^2 =-11y^2+21y

*question_answer*

Q: Simplify this expression by combining like terms. 5x - 12 + 4 - 2x

A: Click to see the answer

*question_answer*

Q: What is the product of the expression (4x²y ²)°(2x ³y²) ' ? O 8z7

A: The given expression is 4x2y-222x-3y2-1.

*question_answer*

Q: Expand to write an equivalent expression-12(-2x+4y)

A: Given that 12(-2x+4y) To Expand to write an equivalent expression

*question_answer*

Q: Find a2, a3, a4, a1= -3, an= 10+2an-1

A: Click to see the answer

*question_answer*

Q: Simplify. (4y²– 2y-3)+(3y²–5y-4)-(8)²-4y-8)

A: Given :

*question_answer*

Q: In Problem,solve each inequality

A: 22x2-3x>-9

*question_answer*

Q: (3z²+a-2) (-4a? - 2z - 1) 2) (-422

A: Explanation of the answer is as follows

*question_answer*

Q: Find A" for A -3 -27 :) A- [ 2) A 5 9 3 4-

A: To find A-1

*question_answer*

Q: Evaluate a + 4 x 7 - 2(b - 1), if a = 7, b = 4

A: We need to evaluate a+4×7-2(b-1)=a+28-2b+2=a-2b+30

*question_answer*

Q: Reduce the expression to lowest terms. (2x + 3) . 3 - (3x - 5) . 2 /(3x - 5) 2

A: Given 32x+3-23x-53x-52

*question_answer*

Q: -13<3x-4< 2

A: Click to see the answer

*question_answer*

Q: Simplify the expression by combining like terms. 2x +4y + 6+ 2y- 5 + 3x

A: Given, 2x+4y+6+2y-5+3x

*question_answer*

Q: Simplify the expression. (-2ab5)(4ab¬4)

A: Click to see the answer

*question_answer*

Q: ア-3、1y-5 4 2. 2.

A: Click to see the answer

*question_answer*

Q: + + + -5 -2+ -4

A: Click to see the answer

*question_answer*

Q: Combine the like terms. A. 2x - 9x = B. 12y - 6y + 8y - 20y = %3D

A: Click to see the answer

*question_answer*

Q: Express as a polynomial.

A: we have to express the equation (4x-5)(2x2+3x-7) in polynomial.

*question_answer*

Q: Find A. -1 (4A)-1 ; -4 2 A =

A: Let the given matrix be B. 4A-1=-11-42=B4A-1=B4A=B-1A=14B-1 Find the inverse of matrix B as follows.…

*question_answer*

Q: Select the expression that is equivalent to the expression -y -3 (-3y + 5)

A: Click to see the answer

*question_answer*

Q: Find A. -3 -2 (4A)-1 = 4 2 A =

A: Click to see the answer

*question_answer*

Q: Find an expression which represents the difference when (-8x + y) is subtracted from (-5x - 8y) in…

A: The two given expressions are -8x+y and -5x-8y.

*question_answer*

Q: Simplify (-7xy4)(-2x5y6)

A: We have (-7xy4)(-2x5y6) We have to simplify it The rule for multiplying exponential expressions…

*question_answer*

Q: -4х - Зу+4 y' = 2х+ у

A: Click to see the answer

*question_answer*

Q: -16 -6v=-2(8v-7)

A: -16-6v=-28v-7-16-6v=-16v+1416v-6v=14+1610v=30v=3010v=3

*question_answer*

Q: do cas 2 (a®) Ja - a 9-9

A: Click to see the answer

*question_answer*

Q: Evaluate : [- b - √(b2 - 4ac)] / 2a , for a = 2, b = 9, and c = -5.

A: Given data: a = 2, b = 9, and c = -5. The given expression: -b±b2-4ac2a

*question_answer*

Q: 2x = -4x?y + 4xy³ 3

A: Given expression: 2x=-4x2y+4xy3

*question_answer*

Q: (-1- 3y = -17 2x-6y=-26

A: The system of equations are -x-3y=-172x-6y=-26. The equation can be represented in matrix form as…

*question_answer*

Q: Subtract 5y^2- 6y- 11 from 6y^2 +. 5

A: Given: fy=5y2-6y-11, gy=6y2+0.5 For substracting fy from gy, we use value of fy and gy

*question_answer*

Q: Simplify: (a2x-1. a***): a*-3

A: Click to see the answer